2014
DOI: 10.1097/aap.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Epidural Hematoma After Spinal Cord Stimulator Trial Lead Placement in a Patient Taking Aspirin

Abstract: The only variable that could have led to our patient's epidural hematoma is aspirin. This is the first reported case of aspirin leading to an epidural hematoma following an interventional chronic pain procedure. Prior to interventional pain procedures, one should contemplate cessation of aspirin therapy because there are, at present, no consensus guidelines to direct such a decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…In addition, there are several reports of bleeding risks during or after epidural procedures in patients taking antiplatelet agents. For instance, Buvanendran and Young [23] published a case report describing a woman who, in the setting of recent aspirin use, developed an epidural hematoma following percutaneous spinal cord stimulator lead placement, and Giberson et al [24] described two patients who developed spinal epidural hematomas following spinal cord stimulator trial lead removal, also in the setting of recent aspirin use. Similarly, Benzon et al [25] reported a patient taking aspirin, clopidogrel, and diclofenac, who developed a cervical epidural hematoma following an epidural steroid injection, and Mayumi and Dohi [26] described a patient taking ticlopidine who developed a spinal subarachnoid hemorrhage following multiple failed attempts at spinal anesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, there are several reports of bleeding risks during or after epidural procedures in patients taking antiplatelet agents. For instance, Buvanendran and Young [23] published a case report describing a woman who, in the setting of recent aspirin use, developed an epidural hematoma following percutaneous spinal cord stimulator lead placement, and Giberson et al [24] described two patients who developed spinal epidural hematomas following spinal cord stimulator trial lead removal, also in the setting of recent aspirin use. Similarly, Benzon et al [25] reported a patient taking aspirin, clopidogrel, and diclofenac, who developed a cervical epidural hematoma following an epidural steroid injection, and Mayumi and Dohi [26] described a patient taking ticlopidine who developed a spinal subarachnoid hemorrhage following multiple failed attempts at spinal anesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…A Tuohy needle had been placed at the T-3 interspace resulting in an inadvertent intramedullary placement of an electrode, with the distal tip at the level of C-2. There is report of significant injury in noncervical spinal cord stimulation, [1][2][3]6,12,13,15,22,29,32 but a paucity of literature studying such injuries in the cervical population.…”
mentioning
confidence: 99%
“…In many cases, the technique is simple with little tissue stress produced to the region; but in some clinical settings, the procedure itself may expose the epidural space to multiple traumatic processes, as there may be multiple needle and lead insertions as well as multiple attempts to steer and redirect the leads. 1,3 Patients with neck or back pain undergoing ESIs or other spinal interventions may have significant spinal abnormalities including spinal stenosis, ligamentum flavum hypertrophy, spondylolisthesis, or spondylosis which may compact the epidural venous plexus within tight epidural spaces. 4,5 Moreover, patients after various spine surgeries may develop fibrous adhesions and scar tissue, thus further compromising the capacity of the epidural space and distorting the anatomy of the epidural vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal hematoma is a very rare complication that has been associated with spinal cord stimulator trials, implants with percutaneous placed cylindrical leads and laminotomy placed paddle leads, lead migration, revisions, and lead removal. [1][2][3]30,[138][139][140] Aspirin has been suggested as a risk factor in some of the cases. 1-3 Case reports of subdural hematomas after spinal anesthesia have also questioned aspirin's continuation before a spinal anesthetic.…”
Section: Procedural Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation